Analysis of ecotoxic influence of waste from the biomass gasification process - Hawrot-Paw, Małgorzata (Environ Sci Pollut Res Int, 2017)
The purpose of this research was evaluation of the effect of soil contamination with waste coming from biomass gasification on chosen indicators of its biological activity, growth and development of spring barley, and change of physiological parameters of the plant. Chromatographic content and basic rheological parameters of the substances under research were also analyzed. Liquid wastes, tar, and mixture of tar and engine oil were introduced to the soil in the amount of 100 mg kg(−1) DM soil. Based on the conducted research, it was ascertained that the changes in the number and activity of soil microorganisms were determined by the type of waste and its dose. Individual groups of microorganisms showed different sensitivity to the presence of pollution; however, the impact of tar and engine oil mixture was generally more disadvantageous. Presence of contaminants in the soil limited the growth of roots and aboveground parts of spring barley, especially when the dose was 10,000 mg kg(−1) DM soil. The unfavorable impact of waste on photosynthesis efficiency on assimilation pigment synthesis and water content in the plant was recorded.